Pertanggungjawaban Hukum Tenaga Medis Atas Kerugian Pasien Akibat Penggunaan Robot Medis - Rois Sagita; Yovita Arie Mangesti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Medical robots with artificial intelligence (AI) are becoming more and more common in Indonesian healthcare, yet there are currently no laws limiting their use or legal accountability. The purpose of this study is to examine medical professionals' legal responsibilities for patient losses resulting from the use of medical robots and examine the legal protections available to patients. Using a juridical-normative method, the study shows that medical personnel can still be held liable for negligence in the use of robots, while losses due to system failure or product defects are the responsibility of the manufacturer and healthcare facility. Patients have the right to protection through informed consent mechanisms, medical device oversight, and the right to sue for damages. This study emphasizes the need for specific regulations to provide legal certainty and stronger protection for patients.